High-fracture toughness and aging-resistance of 3Y-TZP ceramics with a low Al2O3 content for dental applications. Issue 5 (1st April 2019) - Jing, Qiang; Bao, Jinxiao; Ruan, Fei; Song, Xiwen; An, Shengli; Zhang, Yonghe; Tian, Zhen; Lv, Haodong; Gao, Jianquan; Xie, Min
Abstract: The aim of this investigation was to discuss the mechanical properties and aging-resistance of 3Y-TZP (3 mol% yttria-tetragonal zirconia with 0–0.25 wt% alumina added 3Y-TZP) by comparing the effect of high-energy ball milling zirconia powders (HP) and commercially available zirconia powders (CP). The results showed that a hardness of 12.93 GPa, combined with an excellent high-fracture toughness of 9.17 MPa m 1/2, could be attained for HP-doped (0–0.25 wt% (Al2 O3 )) ceramics, as well as an increase in hydrothermal stability with the increase in Al2 O3 content. The HP + 0.15 wt% (Al2 O3 ) ceramics exhibited better antiaging performance and mechanical properties. These 3Y-TZP ceramics, with high-fracture toughness and better aging-resistance, which were prepared by a high-energy ball milling method, could meet the different demands of practical dental ceramics.